(4y + 1)(3y + 2)
Pull out the common factor of 2 ... 2(y^2+6y-16) Then just factor (y^2+6y-16) ... (y-2)(y+8)
4(3y+4)
(x + 3)(x + 4y)
12y + 5 = 53 12y = 48 y = 4
(4y + 1)(3y + 2)
(x + 15)(x - 3)
-6
12y3 - 30y2 + 12yFactor out a y:y(12y2 - 30y + 12)Factor out a 6:6y(2y2 -5y + 2)Factor 2y2 - 5y + 26y(2y - 1)(y - 2)
12Y + 9 all I can see to factor out is 3 3(4Y + 3)
#
Pull out the common factor of 2 ... 2(y^2+6y-16) Then just factor (y^2+6y-16) ... (y-2)(y+8)
The GCF is 12.
4(3y+4)
(x + 3)(x + 4y)
12y + 5 = 53 12y = 48 y = 4
6xy +12y = 6y (x+2)